2008
DOI: 10.1037/a0012851
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the effects of promised and delivered inducements: Relational and transactional contract elements and the mediating role of trust.

Abstract: Psychological contracts contain both relational and transactional elements, each of which is associated with unique characteristics. In the present research, the authors drew on these distinct qualities to develop and test hypotheses regarding differential employee reactions to underfulfillment, fulfillment, and overfulfillment of relational and transactional promises. Further, the authors extended their test of the theoretical distinctions between relational and transactional contracts by assessing the releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
151
2
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(171 citation statements)
references
References 70 publications
16
151
2
2
Order By: Relevance
“…Adult attachment style is focused on long-term personal connections rather than on the short-term or immediate. Montes and Irving (2008) also found trust was an important mediator for relational breach but not transactional breach, suggesting trust is an important part of how relational breach relates to organizational outcomes. Attachment styles as well have a significant focus on trust, with trust in others a crucial factor in each attachment style.…”
Section: Psychological Contractsmentioning
confidence: 96%
See 3 more Smart Citations
“…Adult attachment style is focused on long-term personal connections rather than on the short-term or immediate. Montes and Irving (2008) also found trust was an important mediator for relational breach but not transactional breach, suggesting trust is an important part of how relational breach relates to organizational outcomes. Attachment styles as well have a significant focus on trust, with trust in others a crucial factor in each attachment style.…”
Section: Psychological Contractsmentioning
confidence: 96%
“…Jensen et al (2010) found that breach of relational psychological contract dimensions related to different aspects of counterproductive workplace than transactional dimension breach, with production deviance and withdrawal only relating to relational contract breach. Montes and Irving (2008) found that an employee's trust in the organization was an important mediator of relational breach and organizations outcomes while trust was not a significant mediator for transactional contract breach.…”
Section: Psychological Contractsmentioning
confidence: 98%
See 2 more Smart Citations
“…over-fulfilment) are linked to both positive and negative outcomes (Conway and Briner, 2002;. The expanded view proposes that contract over-fulfilment can be interpreted differently, in terms of being perceived more positively or negatively, dependent on what the promise comprises of (Lambert, 2011;Montes and Irving, 2008). It is possible also that expectation plays a role in the interpretation of an exceeded promise.…”
Section: Introductionmentioning
confidence: 99%